Post-implant installation sensitivity and the importance of prior planning: Case report (Research, Society and Development, 2024)
Implantology has become a fundamental specialty in Dentistry. However, despite the benefits obtained through rehabilitation, complications or errors caused after implant placement are common and are rarely published in the literature. The objective of this study was to report the clinical case of a patient with sensitivity after implant placement (related to tooth 46), in addition to a brief discussion about the main structures affected after implant surgeries and how prior planning and the use of new dental technologies can help to avoid it. This study was characterized by a descriptive design and qualitative analysis. The data came from the clinical practice of the Dentistry course at Faculdade Patos de Minas (FPM), and the participant was a patient of this Institution. During the anamnesis, the main complaint was "tooth pain with cold food." After clinical and radiographic examinations, a periapical lesion was diagnosed in tooth 45, where endodontic treatment and follow-up for 14 months were performed. Through the tomographic image, it was possible to verify the proximity of the dental implant installation with the adjacent structures: apex of tooth 45 and approximately 1 mm from the inferior alveolar nerve (IAN).